Behavior of Composite Piles Reinforced by Geosynthetics - A. El-Kasaby, El-Sayed; Roshdy, Mohab; Awwad, Mahmoud; I. Badawi, Mona I. Badawi (International Journal of Advanced Engineering, Management and Science, 2023)
This study presents the results of five reinforced concrete (RC) pile specimens that were created and horizontally loaded. The RC piles were reinforced by composite materials such as geogrid, geogrid with a core of steel rod, and geogrid with a core of glass fibre reinforced polymers (GFRP) or carbon fiber reinforced polymers (CFRP) rod. This research is expected to investigate the behavior of using composite materials in pile reinforcement and check their efficiency in carrying horizontal loads. The horizontal pile loading test was applied to four pile specimens and a reference pile specimen reinforced by steel rods. All specimens have the same dimensions (150 mm in diameter and 1050 mm in height). A comparison has been carried out between the experimental results for all specimens and the reference specimen. The experimental results illustrated that the specimens carried a lower ultimate horizontal load by 44%–87% compared to the reference specimen. Also, a non-linear finite element analysis has been verified by Abaqus software and achieved a great degree of reconciliation compared to the experimental results. Finally, a comparison of the reinforcement costs for the specimens revealed that utilizing these composite piles could reduce the cost up to 15.2%.